Fabrication and testing of polymer microneedles for transdermal drug delivery - Ebrahiminejad, Vahid; Faraji Rad, Zahra; Prewett, Philip D.; Davies, Graham J. (Beilstein Journal of Nanotechnology, 2022)
Microneedle (MN) patches have considerable potential for medical applications such as transdermal drug delivery, point-of-care diagnostics, and vaccination. These miniature microdevices should successfully pierce the skin tissues while having enough stiffness to withstand the forces imposed by penetration. Developing low-cost and simple manufacturing processes for MNs is of considerable interest. This study reports a simple fabrication process for thermoplastic MNs from cycloolefin polymers (COP) using hot embossing on polydimethylsiloxane (PDMS) soft molds. COP has gained interest due to its high molding performance and low cost. The resin master MN arrays (9 × 9) were fabricated using two-photon polymerization (TPP). A previous gap in the detailed characterization of the embossing process was investigated, showing an average of 4.99 ± 0.35% longitudinal shrinkage and 2.15 ± 0.96% lateral enlargement in the molded MN replicas. The effects of bending, buckling, and tip blunting were then examined using compression tests and also theoretically. MN array insertion performance was studied in vitro on porcine back skin using both a prototype custom-made applicator and a commercial device. An adjustable skin stretcher mechanism was designed and manufactured to address current limitations for mimicking skin in vivo conditions. Finite element analysis (FEA) was developed to simulate single MN insertion into a multilayered skin model and validated experimentally using a commercial Pen Needle as a model for the thermoplastic MNs. Margins of safety for the current MN design demonstrated its potential for transdermal drug delivery and fluid sampling. Experimental results indicated significant penetration improvements using the prototype applicator, which produced array penetration efficiencies as high as >92%, depending on the impact velocity setting.
Keywords: hot embossing; microneedles; penetration efficiency; thermoplastic polymers; two-photon polymerization